2021
DOI: 10.1002/hbm.25455
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced detection of cortical atrophy in Alzheimer's disease using structural MRI with anatomically constrained longitudinal registration

Abstract: Cortical atrophy is a defining feature of Alzheimer's disease (AD), often detectable before symptoms arise. In surface-based analyses, studies have commonly focused on cortical thinning while overlooking the impact of loss in surface area. To capture the impact of both cortical thinning and surface area loss, we used anatomically constrained Multimodal Surface Matching (aMSM), a recently developed tool for mapping change in surface area. We examined cortical atrophy over 2 years in cognitively normal subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
7
1
Order By: Relevance
“…Here, we documented temporal tissue loss by more precise surface based morphometry and at a higher resolution of 360 cortical areas, which has become possible due to increased imaging quality in ADNI3 compared to previous ADNI studies ( Jack et al, 2008 ) and further developed software-aided image assessments. In line with a previous study, we found temporal areas to be differently affected by cortical thickness loss and cortical surface area loss ( Iannopollo and Garcia, 2021 ). High precision evaluation of temporal lobe atrophy is of particular importance as temporal cortex thinning is associated with episodic memory impairments ( Das et al, 2016 ) and even depression ( Fujishima et al, 2014 ) while temporal volume loss was found in healthy aging subjects ( Fjell et al, 2009 ) and may be a potential early indicator of an increased risk for developing AD later in life.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we documented temporal tissue loss by more precise surface based morphometry and at a higher resolution of 360 cortical areas, which has become possible due to increased imaging quality in ADNI3 compared to previous ADNI studies ( Jack et al, 2008 ) and further developed software-aided image assessments. In line with a previous study, we found temporal areas to be differently affected by cortical thickness loss and cortical surface area loss ( Iannopollo and Garcia, 2021 ). High precision evaluation of temporal lobe atrophy is of particular importance as temporal cortex thinning is associated with episodic memory impairments ( Das et al, 2016 ) and even depression ( Fujishima et al, 2014 ) while temporal volume loss was found in healthy aging subjects ( Fjell et al, 2009 ) and may be a potential early indicator of an increased risk for developing AD later in life.…”
Section: Discussionsupporting
confidence: 93%
“…Large between-study heterogeneity of designs and methods, differences in sample characteristics and the generally larger inter-individual variability in samples of older adults make it difficult to extract general trends. To overcome those limitations, longitudinal MRI studies require enhanced neuroimaging pipelines ( Iannopollo and Garcia, 2021 ) and adequate statistical approaches. A very recent two-study comparison design longitudinal MRI study was able to show that it is possible to extract generalizable effects of brain atrophy in healthy aging people ( Jockwitz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lifelong exposures to PM 2.5 above the current USEPA standard are associated with a significant decrease in gray matter from higher order cortical regions, commonly associated with Alzheimer's, Parkinson's and FTD in 42.7 ± 9.3 years old, healthy, college educated, Metropolitan Mexico City residents [45][46][47][48][49][50][51][52][53][54][55][56]. Significant caudate nuclei and cerebellar gray and white matter atrophy were also documented [57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 95%
“…Hemispheric cortical significant differences documented in subjects ≤30 vs. ≥31 years old are of deep concern, as targeted cortical thickness and surface area regions involved overlap with those described in AD, PD, Lewy body disease (LBD) spectrum and FTD [45][46][47][48][51][52][53][54][79][80][81][82]. Brain MRI changes associated with early-onset Alzheimer's disease (EOAD; aged < 65 years) (A + T + N +), in Contador et al, work [51] versus 19 controls (A-T-N-) found EOAD longitudinal atrophy spread with a posterior-to-anterior gradient with hippocampus/amygdala atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Spatially smoothing the data improved the performance of SBM to the point where it matched MBM for smoothing kernels with FWHM 20$$ \ge 20 $$ mm. There are no consistent heuristics for choosing a proper smoothing kernel although 20$$ 20 $$ mm is a common smoothing kernel size (Iannopollo et al, 2021). Smoothing kernels should be chosen carefully since they can impose geometric effects on the data as the kernel replaces the value at each point with a weighted average of its spatial neighbors (Henderson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%